2020
DOI: 10.1051/0004-6361/201936930
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-capture elements in dwarf galaxies

Abstract: Context. We present a large homogeneous set of stellar parameters and abundances across a broad range of metallicities, involving 13 classical dwarf spheroidal (dSph) and ultra-faint dSph (UFD) galaxies. In total, this study includes 380 stars in Fornax, Sagittarius, Sculptor, Sextans, Carina, Ursa Minor, Draco, Reticulum II, Bootes I, Ursa Major II, Leo I, Segue I, and Triangulum II. This sample represents the largest, homogeneous, high-resolution study of dSph galaxies to date. Aims. With our homogeneously d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 267 publications
(353 reference statements)
10
68
1
Order By: Relevance
“…It has been known that the knee position of [𝛼/Fe] varies depending on the luminosity (and thus stellar mass) of dwarf galaxies (Tolstoy et al 2009;Reichert et al 2020). In fact, our model predicts the knee position of [Mg/Fe] at lower metallicity for a less-massive galaxy, in particular for case 1, as also found in the reference galaxies.…”
Section: Evolution Of Mgsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been known that the knee position of [𝛼/Fe] varies depending on the luminosity (and thus stellar mass) of dwarf galaxies (Tolstoy et al 2009;Reichert et al 2020). In fact, our model predicts the knee position of [Mg/Fe] at lower metallicity for a less-massive galaxy, in particular for case 1, as also found in the reference galaxies.…”
Section: Evolution Of Mgsupporting
confidence: 76%
“…Although the observation of a radioactively powered electromagnetic emission (kilonova, Li & Paczyński 1998;Metzger et al 2010) associated with the neutron star merger (NSM) GW170817 (Abbott et al 2017) implies the production of neutron-capture elements such as Sr (Watson et al 2019;Domoto et al 2021) and lanthanides (Arcavi et al 2017;Chornock et al 2017;Nicholl et al 2017;Tanaka et al 2017), no trace of heavy r-process elements such as Eu and Th has been found in the kilonova ejecta. This can be due to difficulties in identification of elements in highly Doppler-shifted spectra as well as a lack of the relevant atomic data; however, it is suggested that the overall collapsars (Siegel et al 2019) or magneto-rotational supernovae (MRSN, Winteler et al 2012;Nishimura et al 2015;Reichert et al 2020); but see Fujibayashi et al 2020b andMösta et al 2018 for implications of the former and latter case, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The [Ba/Mg] abundances of very metal-poor stars in some dwarf galaxies also support the existence of significant time delays. Although the sample is small and dwarf galaxies have a different SFH, most stars are on the same track as the MW stars (Figure 4 and see also Reichert et al 2020). Therefore the "delay" is likely a common feature, which can be tested with larger samples of the Ba abundances of dwarf galaxies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Low-α halo stars have likely been accreted from dwarf galaxies, which, compared to the MW, offer less gas and in turn form a larger population of lower-mass supernovae, thereby explaining the lower α−abundances (see e.g. McWilliam et al 2013;Reichert et al 2020, for different views).…”
Section: Chemically Peculiar Starsmentioning
confidence: 99%